(2x-3)=(3x-5)

Simple and best practice solution for (2x-3)=(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x-3)=(3x-5) equation:


Simplifying
(2x + -3) = (3x + -5)

Reorder the terms:
(-3 + 2x) = (3x + -5)

Remove parenthesis around (-3 + 2x)
-3 + 2x = (3x + -5)

Reorder the terms:
-3 + 2x = (-5 + 3x)

Remove parenthesis around (-5 + 3x)
-3 + 2x = -5 + 3x

Solving
-3 + 2x = -5 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
-3 + 2x + -3x = -5 + 3x + -3x

Combine like terms: 2x + -3x = -1x
-3 + -1x = -5 + 3x + -3x

Combine like terms: 3x + -3x = 0
-3 + -1x = -5 + 0
-3 + -1x = -5

Add '3' to each side of the equation.
-3 + 3 + -1x = -5 + 3

Combine like terms: -3 + 3 = 0
0 + -1x = -5 + 3
-1x = -5 + 3

Combine like terms: -5 + 3 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 10x^6+8x^4=0 | | x=27+-2x | | x-10/x+2=7 | | -2.7=-1.3+0.7x | | x-(8x^(1/2))+4=0 | | 8/11(n+10)=64 | | -3x+12=9 | | 9-y=9 | | 15x-45+3x=18x+18-13 | | x+0.07x=16.05 | | 9x-1=8x+19 | | (9x+2)/5=4 | | (3x^2+2x-9)-(-3x+4)= | | -3-y=9 | | (3y/2a)/(8a^2y5/15y) | | 6x^2+2x-58=0 | | 2.3x-9.34=6.3 | | 4/17(x)=20 | | 3x-14=2x+19 | | -40-3x=14-10x | | 3-2(1/7) | | 8c+c=27 | | -4y-2+3y+4=-5 | | 24w^9x^6y-22x^4y^6= | | 2(1/7) | | 1x-6=3x-4 | | -[4(7)+2]-[3(7)-4]=x | | 4b+29=48 | | -[4(7)+2]-[3(7)-4]=-5 | | 3-21/7 | | y=3x+6graph | | 60=-5x+9 |

Equations solver categories